Analisis Kelayakan Ekonomi dan Finansial Penerapan Discount Factor pada Berbagai Kelompok Bank terhadap Usahatani Padi Organik di Kabupaten Buton Utara - Abdi, Abdi; Mukhtar, Mukhtar; Hamzah, Awaluddin; Jabuddin, La Ode (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
Organic food agriculture, especially rice, is a potential business opportunity in the present and in the future. This is based on the principle of the benefits of organic food, which puts forward the principles of good health for plants, soil, animals, earth, and humans as an interconnected and inseparable whole. The objectives of this study were to analyze the economic and financial feasibility of organic rice farming in North Buton Regency, to analyze the economic and financial viability of farming when input prices change, and to compare the feasibility of organic rice farming in various bank groups. The data used in this study are primary and secondary data, the variable coverage of which consists of the amount of organic rice production, production price, and the components of farm costs. Respondents were determined using accidental sampling technique, in order to obtain 60 farmer household respondents. Furthermore, an economic and financial feasibility analysis approach is used which consists of 3 criteria, namely net present value, net benefit-cost ratio, and internal rate of return. The results showed that: (1) organic rice farming in North Buton Regency based on economic and financial feasibility criteria is feasible to be cultivated and or developed, (2) Even though there has been a change in input prices, organic rice farming in Buton Utarata Regency is feasible to be cultivated and or developed, (3) the selection of business investment credit in the state-owned bank group and the national private bank group is more feasible to operate, while the business investment credit in the regional government bank group is vulnerable to the risk of loss. Therefore, in applying for investment credit for organic rice farming, farmers must choose a financial institution in the state bank group or national private bank.